The Value of Voting Rights to Majority Shareholders: Evidence from Dual-Class Stock Unifications - Hauser, Shmuel; Lauterbach, Beni (Review of Financial Studies, 2004)
We study transactions of voting rights. In our sample of 67 dual class unifications superior vote shareholders give up their superior voting status (all firm stocks become "one share one vote"), and receive (in most cases) compensation in the form of additional stocks. Based on the compensation granted, the median price of 1% of the vote is about 0.1% of firm's equity. More interestingly, the price of vote decreases with institutional holdings, and increases with the percentage vote lost by the majority shareholders. The position and interests of the majority holders appear as the main determinants of the price of vote. * School of Management, Ben-Gurion University of the Negev, Beer-Sheva, Israel, and Chief Economist, Israel Securities Authority, Jerusalem 95464, Israel. ** Corresponding Author: The Anderson School at UCLA, 110 Westwood Plaza, Los Angeles CA 90095, USA; and School of Business Administration, Bar-Ilan University, Ramat Gan 52900, Israel. Fax: 310-2065455; e-mail: ...